2023
DOI: 10.1523/jneurosci.2195-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic Assemblies Link Domains of Presynaptic and Postsynaptic Intracellular Structures across the Synaptic Cleft

Abstract: The chemical synapse is a complex machine separated into three parts: presynaptic, postsynaptic, and cleft. Super-resolution light microscopy has revealed alignment of presynaptic vesicle release machinery and postsynaptic neurotransmitter-receptors and scaffolding components in synapse spanning nanocolumns. Cryo-electron tomography confirmed that postsynaptic glutamate receptor-like structures align with presynaptic structures in proximity to synaptic vesicles intotranssynaptic assemblies. In our electron tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Subsequent electron microscopy studies, using both cultured neurons and brain tissue-derived samples, together with imaging studies of biochemically isolated synaptosomes, have provided progressively higher resolution visualizations of synapses and their surrounding structures [6][7][8]. More recently, electron microscopy experiments, together with light microscopy studies, suggest that in excitatory, glutamatergic synapses, there is a transsynaptic organization of presynaptic and postsynaptic components that aligns sites of transmitter release and detection [9][10][11][12][13].…”
Section: Main Textmentioning
confidence: 99%
“…Subsequent electron microscopy studies, using both cultured neurons and brain tissue-derived samples, together with imaging studies of biochemically isolated synaptosomes, have provided progressively higher resolution visualizations of synapses and their surrounding structures [6][7][8]. More recently, electron microscopy experiments, together with light microscopy studies, suggest that in excitatory, glutamatergic synapses, there is a transsynaptic organization of presynaptic and postsynaptic components that aligns sites of transmitter release and detection [9][10][11][12][13].…”
Section: Main Textmentioning
confidence: 99%
“…This study identified the existence of trans-synaptic nanocolumns, which co-organize the pre-synaptic release machinery in register with post-synaptic AMPARs and improve the efficiency of synaptic transmission [87,88] (figure 1b,c). Interestingly, the recent developments in cryo-electron tomography have allowed the ultrastructural visualization of these protein nanodomains and trans-synaptic assemblies [102][103][104][105][106][107][108]. The burning question that thus arose was: what are the underlying molecular elements that bridge pre-and post-synaptic nanodomains?…”
Section: Post-synaptic Nano-organization and Trans-synaptic Complexes...mentioning
confidence: 99%
“…The extracellular space between the pre- and postsynaptic compartments constitutes the synaptic cleft, considered to be the third compartment of the synapse. By electron microscopy (EM), the synaptic cleft is observed to contain electron dense proteinaceous material ( Lucic et al, 2005 ; Zuber et al, 2005 ; Burette et al, 2012 ; High et al, 2015 ; Cole and Reese, 2023 ), including cell adhesion molecules, extracellular proteins and extracellular moieties of various receptors and ion channels ( Missler et al, 2012 ; Loh et al, 2016 ; Cijsouw et al, 2018 ). Trans-synaptic bridges formed through association of cell adhesion molecules from opposite sides of the junction maintain a space of mostly regular width and define the synaptic contact area.…”
Section: Introductionmentioning
confidence: 99%